GaAs metamorphic high electron mobility transistors for future deep space-biomedical-millitary and communication system applications: A review. (October 2019) - Ajayan, J.; Nirmal, D.; Mohankumar, P.; Kuriyan, Dheena; Fletcher, A.S. Augustine; Arivazhagan, L.; Kumar, B. Santhosh
Abstract: Following the introduction of metamorphic high electron mobility transistors (MHEMTs) 30 years back, there has been a rapid growth in their use in advanced MMIC (monolithic microwave integrated circuit) and TMIC (Terahertz monolithic integrated circuit) applications in sub-millimetre wave (S-MMW) and terahertz (THz) frequency regime. Undoubtedly, they are capable of making a great impact in applications such as deep space, cryogenic, biomedical instrumentation, military, high speed communication networks etc, in the years to come. This review article not only studies the progress of depletion mode (D-Mode), enhancement mode (E-Mode) type MHEMTs in the last 30 years, extensively but also critically and systematically analyzes the fabrication challenges, reliability issues and their use in cryogenic fields. Yet another highlight is that the work also carefully examines the utility of MHEMTs in deep space, biomedical, scientific, military, communication areas and so forth.